The C subunit of the nuclear factor Y binds to the Cyclin P4;1 promoter to modulate nodule organogenesis and infection during symbiosis in Phaseolus vulgaris - Roda, Carla Lucía (2024)
During nitrogen-fixing symbiosis, bacteria areallocated into postembryonic root organs called nodules. Recognition of these bacteriatriggers the activation of transcription factors of the nuclear factor Y (NF-Y)family, which play functions at different stages of the root nodule symbiosis.We have previously shown that PvNF-YA1 and PvNF-YC1 play a crucial role duringnodulation, modulating the expression of G2/M transition cell cycle genes in commonbean (Phaseolus vulgaris). Here, we demonstrate that PvNF-YC1 directlybinds to the promoter of the cyclin P gene PvCYCP4;1. Notably, the PvCYCP4;1transcript level was reduced not only in PvNF-YC1 and PvNF-YA1 knockdownplants, but also upon silencing of the GRAS type transcription factor Scarecrowinvolved in Nodulation (SIN1), suggesting that both the NF-Y complexand SIN1 control the expression of this cyclin gene. PvCYCP4;1 isexpressed in root meristems and during early and transient cell divisions thatgive origin to determinate nodules. Post-transcriptional silencing of PvCYCP4;1produced a marked reduction in the number and size of the nodules andnegatively affected the frequency of infection events. Altogether, our results suggestthat the module formed by the NF-Y complex, PvCYCP4;1, activate the corticalcell divisions that promote nodule organogenesis and control rhizobiuminfection.